Pengaruh Lingkungan Kerja dan Berbagi Pengetahuan Terhadap Kinerja Karyawan Industri Kreatif Melalui Kemampuan Inovasi Individu - Silvia Mutiara Natasha; Jul Aidil Fadli (Masyarakat Ekonomi Syariah Bogor, 2025)
The creative industry is a sector that demands employees to continuously innovate and adapt quickly in a dynamic work environment. This study aims to examine the influence of work environment and knowledge sharing on employee performance through individual innovation capability in the creative industry sector. A quantitative approach with a descriptive-causal design was used in this research. Data were collected through digital questionnaires distributed to 110 respondents who are active employees in the creative industry in the Jakarta area, using purposive sampling based on specific criteria. Data analysis was conducted using Structural Equation Modeling with the Partial Least Square (SEM-PLS) method. The results show that knowledge sharing and individual innovation capability have a direct and significant influence on employee performance, while the work environment does not show a significant direct effect. However, individual innovation capability is proven to mediate the relationship between both the work environment and knowledge sharing on employee performance positively and significantly. The implications of this research emphasize the importance of building a work culture that supports collaboration and knowledge exchange to foster innovation and improve performance. Future research is recommended to increase the number of respondents, expand the area coverage, and classify respondents based on their job units to allow for more specific and in-depth analysis.